Targeted review of maximum residue levels (MRLs) for fenarimol - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Marco Binaglia; Luis Carrasco Cabrera; Irene Castellan; Anna Federica Castoldi; Arianna Chiusolo; Federica Crivellente; Monica Del Aguila; Lucien Ferreira; German Giner Santonja; et al. (EFSA Journal)
Abstract In accordance with Article 43 of Regulation (EC) 396/2005, EFSA received a request from the European Commission to review the existing maximum residue levels (MRLs) for the non‐approved active substance fenarimol in view of the possible lowering of the MRLs. EFSA investigated the origin of the current EU MRLs. For existing EU MRLs that reflect previously authorised uses in the EU, or that are based on obsolete Codex maximum residue limits, or import tolerances that are not required any longer, EFSA proposed the lowering to the limit of quantification. EFSA performed a chronic and acute dietary risk assessment for the revised list of MRLs to allow risk managers to take the appropriate decisions. For some commodities, further risk management discussions are required to decide which of the risk management options proposed by EFSA should be implemented in the EU MRL legislation.